HUBUNGAN ANTARA KECEPATAN AWALAN DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT TINGGI GAYA FLOP PADA SISWA PROGRAM EKSTRAKULIKULER SMAN 2 PANDEGLANG - Muhammad Yusup (Program Studi Pendidikan Jasmani Universitas Negeri Jakarta, 2022)
The study aims to determine the relationship between starting speed and the results of the flop style high jump.Analysis of the research data obtained the following results: first, there is a relationship between Starting Speed ​​and the Results of the Flop Style High Jump, with the equation of the line ler Ŷ = 226.750 + -24.977X₁ correlation coefficient ry₁ = -0.575 And the coefficient of determination (ry₁²) = 0.331 the Starting Speed ​​variable contributes to the Results of the Flop Style High Jump 33.1%. Second, there is a relationship between Leg Muscle Explosive Power and the Results of the Flop Style High Jump, with the equation Ŷ = 97.440 + 6.566X₂, correlation coefficient ry₂ = 0.286, coefficient of determination (ry₂²) = 0.286, Leg Muscle Explosive Power contributes 28.6% to the Results of the Flop Style High Jump.